Meteorological drought analysis based on rainfall data of temperate region of Kashmir - KUMAR, ROHITASHW; KUMAR, MUKESH; MAJID, MALIQA (Journal of Soil and Water Conservation, 2018)
Drought monitoring is an important aspect for water budgeting, planning and management. The present study was conducted to analysis drought of Srinagar area of Jammu and Kashmir using Standardized Precipitation Index (SPI) approach which is based on probability concept. The SPI method has several important characteristics over previous indices, including its simplicity, temporal flexibility and minimal data requirement. Monthly precipitation data from 1985 to 2014 for Srinagar were used to compute SPI values. The SPI series was plotted for short, intermediate as well as for long time scales. The SPI results shown that the drought occurred in years 1999, 2000, 2001, 2007 during 1985 to 2014. The extreme severe drought results were found in the year of 1999 when the rainfall deficit was 43.85%. The results showed that for kharif season, moderate drought occurred in the years 1989, 2002, 2004, 2010 and 2012; severe drought occurred in the years 2000, 2001 and 2008; whereas extreme drought occurred only in the year 1999. For rabi season, moderate drought occurred in the years 1989, 2002, 2004, 2010 and 2012; severe drought occurred in the years 2000, 2001 and 2008; whereas extreme drought occurred in the years 1999 and 2001. For zaid season, moderate droughts occurred in the years 1987, 1990, 1993 and 2004; severe drought occurred in the years 1997, 1998, 2000, 2001, 2003 and 2008; whereas extreme drought occurred in years 1989 and 1999. Thus, the most critical drought year was found in 1999. The results of the study are also relevant to climate change studies to understand the historic patterns and build future scenarios of drought.